Frequency of additional treatments in relation to the number of root filled canals in molar teeth in the Swedish adult population. (6th February 2021) - Markvart, M.; Tibbelin, N.; Pigg, M.; Fransson, H.
Abstract: Aim: To investigate the 5‐year frequency of additional treatments in relation to the number of reported root filled canals in molar teeth in Sweden. Methodology: The cohort included first and second molars in adult individuals who were registered with a root filling performed in 2009. Treatment codes corresponding to root fillings of teeth with from one up to four root filled canals were identified in the Swedish Social Insurance Agency database. The studied additional treatments were extraction, non‐surgical root canal retreatment and endodontic surgery during the subsequent 5 years, identified by corresponding codes for these treatments registered on these specific teeth. Differences in the frequency of additional treatments based on the number of root filled canals were analysed using chi‐square test and considered statistically significant at P  < 0.05. Results: In 2009, root fillings on a first or second molar tooth were registered in 100 720 individuals. The study included 32 901 maxillary first molars (6.4% with four root filled canals), 12 763 maxillary second molars (3.3% with four root filled canals), 37 703 mandibular first molars (19.2% with four root filled canals) and 17 353 mandibular second molars (3.7% with four root filled canals). The total frequency of additional treatments was 14.3% ( n  = 14 425) during the 5‐year observational period. Additional treatments were more frequent in teeth with 1–3 root filled canals compared to teeth with four root filled canals for maxillary first molars (15.2% vs. 12.7%, P  = 0.002), maxillary second molars (13.8% vs. 9.1%, P  = 0.007) and mandibular first molars (14.0% vs. 10.7%, P  < 0.001) but not mandibular second molars (15.6% vs. 13.7%, P  = 0.200). Conclusions: Over 5 years, 85.7% of the included teeth were not registered with any additional treatments. Maxillary first and second molars and mandibular first molar teeth had a greater frequency of additional treatments when ≤3 root canals were filled compared to four canals.